Korean Drama Blind: Analysis Using Charles S. Peirce's Mutually Exclusive Theory (Universitas Pendidikan Indonesia, 2024)
Korean drama or Drakor is one of the shows that is popular with various groups. One of the dramas that has a high rating in 2022 is entitled